2010
DOI: 10.5194/acp-10-3405-2010
|View full text |Cite
|
Sign up to set email alerts
|

Global atmospheric budget of acetaldehyde: 3-D model analysis and constraints from in-situ and satellite observations

Abstract: We construct a global atmospheric budget for acetaldehyde using a 3-D model of atmospheric chemistry (GEOS-Chem), and use an ensemble of observations to evaluate present understanding of its sources and sinks. Hydrocarbon oxidation provides the largest acetaldehyde source in the model (128 Tg a<sup>&minus;1</sup>, a factor of 4 greater than the previous estimate), with alkanes, alkenes, and ethanol the main precursors. There is also a minor source from isoprene oxidation. We use an updated chem… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
288
3
5

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 293 publications
(309 citation statements)
references
References 121 publications
13
288
3
5
Order By: Relevance
“…There was no correlation between methanol and the dissolved organic carbon (DOC) content of rainwater samples, indicating that the methanol makes up a variable fraction of the organic carbon pool. Methanol concentrations were strongly correlated with acetaldehyde, which has a primarily biogenic input (Millet et al, 2010), suggesting that the potential biogenic source of methanol is consistent with the larger concentration of methanol observed during the growing season (Fig. 5).…”
Section: Intercorrelationsupporting
confidence: 55%
“…There was no correlation between methanol and the dissolved organic carbon (DOC) content of rainwater samples, indicating that the methanol makes up a variable fraction of the organic carbon pool. Methanol concentrations were strongly correlated with acetaldehyde, which has a primarily biogenic input (Millet et al, 2010), suggesting that the potential biogenic source of methanol is consistent with the larger concentration of methanol observed during the growing season (Fig. 5).…”
Section: Intercorrelationsupporting
confidence: 55%
“…The lack of an observed vertical gradient in ethanol concentrations over the ocean also precludes an oceanic source; reducing the oceanic sink by decreasing the deposition velocity over oceans (0.28 to 0.08 cm/s) does not explain the discrepancy. This inability to simulate high observed mixing ratios in the free troposphere has been shown to occur for acetaldehyde in another global chemical transport model (Millet et al, 2010), indicating a general inconsistency between the observations and our understanding of the budget of short-lived volatile organic compounds.…”
Section: Resultsmentioning
confidence: 90%
“…The dependence of ethanol emissions on root flooding or plant stress is not considered here. With the availability of more information, the calculation of biogenic ethanol emissions has recently been revised to include the dependence on light and root flooding in MEGANv2.1 (Millet et al, 2010). We calculate monthly mean emissions offline using average emission factors (Fig.…”
Section: Ethanol Sourcesmentioning
confidence: 99%
“…Kieber et al (1990) showed that compounds like formaldehyde, acetaldehyde or glyoxylate are produced from the photochemical oxidation of Dissolved Organic Matter (DOM) in natural waters when exposed to sunlight. Millet et al (2010) recently parameterized data from Kieber et al (1990) and showed that DOM photochemistry in the ocean is the second largest global source for acetaldehyde (57 Tg/year). Relying on the satellite retrievals of CHOCHO, the spatial distribution of the acetaldehyde source indeed appears to somewhat resemble that of CHOCHO at tropical latitudes (Wittrock et al, 2006;).…”
Section: Discussionmentioning
confidence: 99%